Assessment of Spiritual, Social, and Practical Competencies in Islamic Religious Education Through Performance-Based Assessment - Amiliya Nur Rosyidah; Fatimah Azzahrah; Indah Aminatuz Zuhriyah; Figo Zulfan Alfaraby; Ceni Amaliya; Akhmad Fatkhul Wahab (Al-Ishlah: Jurnal Pendidikan Islam, 2025)
ABSTRACT Assessment in Islamic Religious Education (PAI) can no longer be limited to cognitive aspects alone, but must include spiritual, social, and practical dimensions that reflect the practice of Islamic values in everyday life. This study aims to explain the concept and implementation strategies of Performance-Based Assessment (PBA) in assessing the spiritual, social, and practical competencies of students. This study uses a descriptive-qualitative approach based on literature review and analysis of educational policy documents. The findings indicate that PBA can authentically assess religious practices, social behavior, and the application of Islamic values in real life through observation, reflective journals, collaborative projects, and situational simulations. Although the implementation of PBA faces challenges such as subjectivity in assessment and resource limitations, solutions can be found through the development of objective rubrics, teacher training, and the integration of assessment into daily learning activities. Therefore, PBA serves as an effective and transformative evaluation tool in more contextual and meaningful Islamic Education learning. Keywords: Performance-Based Assessment, Islamic Religious Education, spiritual, social, and practical assessment.